Green Mission Game for the Forest Preservation Campaig - Nuryanti Nuryanti; Ridwan Sanjaya; Hendra Prasetya (SISFORMA, 2018)
Forest have an important role for living thing, like human, animal, or plants. For example, forests play an active role in the availability of water sources that participated maintain food security for living beings and the largest supplier of oxygen. However, the lack of human consciousness in maintaining forest ecosystems resulted in the emergence of several threats that cause forest destruction in the form of deforestation and degradation include illegal logging, forest fires, forest conversion for plantations and industries [3]. With game application: Green Mission, it is be expected to be one of the solutions and can answer the problem for dealing with the forest damage. Application Green Mission is supposed to educate about the importance of conserving forest by planting trees. In this game, players are directed to resolve some of the challenges in the form of putting out fires, replant the forest bare, and drove the actors of deforestation. The concept in an adventure game is supposed to give a pleasant impression beside to educate player.